Personal factors, psychological work climate, and role related factors as precursors of organizational commitment of records management employees in state civil services of Northwest, Nigeria (2016)
The purpose of the present study was to find out if personal factors, psychological work climate, and role related factors are the precursors of organizational commitment. The study data were collected from a sample of 651 records management employees in State Civil Services of North-west, Nigeria, using a self-designed biographical and occupational questionnaire; a psychological work climate questionnaire adopted from Brown and Leigh; a role-related factors questionnaire adopted from Rizzo et al.; and an organizational commitment (OC) questionnaire adopted from Meyer and Allen. The present study found that age, educational qualification, job tenure psychological work climate, role conflict and role ambiguity have significant correlations with organizational commitment of records management employees in State Civil Services of North-west, Nigeria. It was further found that age, educational qualification, job tenure, psychological work climate, role conflict and role ambiguity have an additive effect on organizational commitment of records management employees in State Civil Services of North-west, Nigeria. Recommendations on how to improve organizational commitment of records management employees were also given.